East Benue-Congo: Nouns, Pronouns, And Verbs - Watters, John (My University, 2018)
This volume is the first in what hopefully will be a growing set of edited volumes and monographs concerning Niger-Congo comparative studies. This first volume addresses matters that are relevant to the entire East Benue-Congo family as well as the particular branches Kainji, Plateau, and Bantoid. In the case of Bantoid, the particular focus is on Grassfields and the Grassfields-Bantu borderland, though other Bantoid subgroups are referenced. The potential topics for comparative studies among these languages are numerous, but this volume is dedicated to presentations on nominal affixes, third person pronouns, and verbal extensions. A forthcoming volume will provide some results of reconstructions and lexicostatistics in Cross River, exploratory reconstructions in Southern Jukunoid, and reconstructions in Ekoid-Mbe and Mambiloid.
Keywords: East Benue-Congo; Nouns; Pronouns; Verbs